2003
DOI: 10.1128/jcm.41.6.2477-2482.2003
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of SHV-12 and Characterization of New AmpC-Type Beta-Lactamase Genes among Clinical Isolates of Enterobacter Species in Korea

Abstract: To determine the prevalence and genotype of an extended-spectrum beta-lactamase and new chromosomal AmpC beta-lactamases among clinical isolates of Enterobacter species, we performed antibiotic susceptibility testing, pI determination, induction tests, transconjugation, enterobacterial repetitive consensus (ERIC) PCR, sequencing, and phylogenetic analysis. Among the 51 clinical isolates collected from a university hospital in Korea, 6 isolates have been shown to produce SHV-12 and inducible AmpC beta-lactamase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 22 publications
3
9
0
1
Order By: Relevance
“…Moreover, the proportion of ESBL-producing isolates was even higher (15%, 25%, and 37%, respectively) in intensive care units than elsewhere. SHV-12 remained the most prevalent type of ESBL among Enterobacter cloacae, which was in agreement with previous findings (13,27).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, the proportion of ESBL-producing isolates was even higher (15%, 25%, and 37%, respectively) in intensive care units than elsewhere. SHV-12 remained the most prevalent type of ESBL among Enterobacter cloacae, which was in agreement with previous findings (13,27).…”
Section: Discussionsupporting
confidence: 82%
“…A 99.5% homology with the A. cloacae K9973-β-lactamase AmpC gene sequence was identified. The overall length of A. cloacae K9973-β-lactamase AmpC gene sequence was 1,165 bp, consistent with the gene sequence of A. cloacae K9973-generating CMY-7 AmpC enzyme previously identified by Lee et al (24). The present study is the first reported identification of plasmid-mediated AmpC β-lactamase expression in P. aeruginosa.…”
Section: Discussionsupporting
confidence: 70%
“…ESBLs of the SHV-2, SHV-5, and SHV-12 lineage initially dominated in those studies in which genotypic characterization has been carried out (209). Newly described SHV-type ESBLs have recently been reported from Taiwan and Japan (82,202).…”
Section: Global Epidemiologymentioning
confidence: 99%